Integrated control of sesame wilt disease caused by the fungus Fusarium solani (Mart.) Sacc. Using Trichoderma harzianum and the decomposed organic fertilizer - Hussein, Murtada Hammadi; Alwan, Sabah Lateef; AL-Abedy, Aqeel Nazzal (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted in Qadisiya, Iraq, in 2016, to control the disease of sesame wilting, caused by the fungus Fusarium solani, using organic fertilizer, Trichoderma harzianum, N.P.K. and the fungicide Beltanol for comparison. The treatment with organic fertilizer inhibited the fungus F. solani (66.66%) and stimulated the growth of biological control T. harzianum by 27.71% compared to the control treatment which reached 0.00%. The treatment with the fungicide Beltanol had a high inhibitory effect on the growth of F. solani with percentage of 100%, while it did not inhibit T. harzianum at the concentration of 1 ml / l. in conclusion, the addition of the organic fertilizer and the T. harzianum provided a high protection for seed, seedling and plants from the effect of F. solani, with an increase in the growth parameters of sesame plants.